Pendekatan Kurikulum Integratif dalam Optimalisasi Manajemen Tahfizh Al-Qur’an - Pangestu Aji Swasono; EE. Junaedi Sastradiharja; Farizal MS (Penerbit Minhaj Pustaka, 2024)
This research explores the optimization of Quranic memorization management through an integrative curriculum approach. The primary focus is to understand how the implementation of an integrative curriculum can enhance the memorization achievements of students. Using a qualitative research method through a literature review, this study delves into the concepts and application of an integrative curriculum in the context of Quranic education. The underlying hypothesis is that a well-implemented integrative curriculum can improve the effectiveness of tahfizh management, thereby enhancing students' memorization performance. The findings indicate that an integrative curriculum, which combines religious and general knowledge, significantly contributes to the improvement of students' memorization quality, supported by effective management and teaching methods tailored to students' characteristics. The study concludes by emphasizing the importance of applying an integrative curriculum in Quranic educational institutions as an effective strategy for improving students' learning outcomes. This research provides valuable insights into the development of Islamic education management, particularly in the context of Quranic memorization programs. Abstrak Penelitian ini membahas optimalisasi manajemen tahfizh Al-Qur'an melalui pendekatan kurikulum integratif. Fokus utama dari penelitian ini adalah untuk memahami bagaimana penerapan kurikulum integratif dapat meningkatkan prestasi hafalan santri. Dengan menggunakan metode penelitian kualitatif melalui studi pustaka, penelitian ini mengeksplorasi konsep dan penerapan kurikulum integratif dalam konteks pendidikan tahfizh. Hipotesis yang mendasari penelitian ini adalah bahwa penerapan kurikulum integratif yang tepat dapat meningkatkan efektivitas manajemen tahfizh, sehingga memperbaiki capaian hafalan santri. Temuan penelitian menunjukkan bahwa kurikulum integratif yang menggabungkan antara ilmu agama dan ilmu umum memberikan kontribusi signifikan terhadap peningkatan kualitas hafalan santri, didukung oleh manajemen yang baik serta metode pengajaran yang sesuai dengan karakteristik santri. Kesimpulan dari penelitian ini menegaskan pentingnya penerapan kurikulum integratif dalam institusi pendidikan tahfizh sebagai strategi efektif dalam meningkatkan hasil belajar santri. Penelitian ini memberikan kontribusi penting bagi pengembangan manajemen pendidikan Islam, khususnya dalam konteks pendidikan tahfizh.